2019
DOI: 10.1136/rapm-2018-100036
|View full text |Cite
|
Sign up to set email alerts
|

Acute postoperative pain is an independent predictor of chronic postsurgical pain following total knee arthroplasty at 6 months: a prospective cohort study

Abstract: BackgroundApproximately 15% of patients report persistent knee pain despite surgical success following total knee arthroplasty (TKA). The purpose of this study was to determine the association of acute-postsurgical pain (APSP) with chronic postsurgical pain (CPSP) 6 months after TKA controlling for patient, surgical and psychological confounding factors.MethodsAdult patients with osteoarthritis undergoing primary elective tricompartmental TKA, with the operated knee the primary source of preoperative pain, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 26 publications
3
80
2
2
Order By: Relevance
“…Delays or failure to recognize this entity can lead to long-term consequences. Buvanendran et al showed that acute postoperative pain is a predictor of patients transitioning to chronic pain [12]. They found that anxiety, pain catastrophizing, depression, and limited physical mobility were factors contributing to the development of chronic pain [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delays or failure to recognize this entity can lead to long-term consequences. Buvanendran et al showed that acute postoperative pain is a predictor of patients transitioning to chronic pain [12]. They found that anxiety, pain catastrophizing, depression, and limited physical mobility were factors contributing to the development of chronic pain [12].…”
Section: Discussionmentioning
confidence: 99%
“…Buvanendran et al showed that acute postoperative pain is a predictor of patients transitioning to chronic pain [12]. They found that anxiety, pain catastrophizing, depression, and limited physical mobility were factors contributing to the development of chronic pain [12]. In a study of more than 30,000 patients, Lewis et al reported catastrophizing and preoperative pain as major factors for persistent postsurgical pain [13].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the parent study have been reported separately 1. This manuscript adheres to the Strengthening the Reporting of Observational Studies in Epidemiology guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…The Short-Form McGill Pain Questionnaire-2 was also administered 16. CPSP was defined as NRS pain with movement ≥4 at 6 months 1. To minimize false-positive assignment of CPSP based on a single NRS value, pain trajectories between 3 weeks and 6 months were evaluated, and a pattern of NRS pain at rest >0 and at least one prior recording of NRS pain during movement ≥4 were required to be classified as CPSP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation